Upaya Pemanfaatan Digitalisasi Pemasaran Dalam Meningkatkan Daya Saing UMKM Di Desa Dongko - Dian Ayu Lestari; Jihan Amira Nurcahyo; Pahala Raja Pangindoan Simanullang; Wiwin Yulianingsih (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Digitalization of marketing emerged in the Industrial Revolution 4.0 Era, which in the era of digital technology and the internet must be interconnected. This is a challenge for Micro, Small and Medium Enterprises (MSMEs) to have creative, innovative businesses and minimize operational costs. Through student service activities for the community by providing assistance to MSME actors in Dongko Village in optimizing digital marketing by holding socialization related to marketing digitalization. The method used in this activity is to use a quality approach through outreach, implementation and mentoring. the result of this activity is to help digitize the marketing of MSME products in Dongko Village. So that these activities affect MSME actors in Dongko Village to take advantage of digital marketing gradually.